Late Pleistocene–Holocene ground surface heat flux changes reconstructed from borehole temperature data (the Urals, Russia) - Demezhko, D. Y.; Gornostaeva, A. A. (Climate of the past, 2015)
We use geothermal reconstruction of the ground surface temperature (GST) history early obtained in the Middle Urals to determine the surface heat flux (SHF) history over the past 35 kyr. A new algorithm of GST–SHF transformation was applied to solve this problem. The timescale of geothermal reconstructions has been corrected by comparing the estimated heat flux and annual insolation at the latitude of 60° N. The consistency of SHF and insolation changes on the interval 35–6 kyr BP with the linear correlation coefficient R = 0.99 points to orbital factors as the main cause of climatic changes during the Pleistocene–Holocene transition. The amplitude of SHF variations is about 1.3% of the insolation change amplitude. The increase of carbon dioxide concentrations lagged by 2–3 kyr from the SHF increase and occurred synchronously with GST changes.